Cultural appropriateness of International Child Abuse screening tools for child abuse and neglect: a qualitative study. (August 2017) - Mitwalli, Suzan; Amro, Zeina; Hamayel, Layaly; Hammoudeh, Doaa; Imseeh, Sawsan; Rabia, Yoke; Halileh, Samia; Giacaman, Rita
Abstract: Background: Although much research has been done into fertility and childbearing in the Palestinian context, research into the practice of child-raising is scarce. In preparation for a study on child discipline and abuse in the West Bank, we investigated the cultural appropriateness of two International Child Abuse screening tools: one for parents or caretakers (ICAST-P) and the other for young people aged 18–24 years (ICAST-R), which were both developed by the International Society for Prevention of Child Abuse and Neglect (ISPCAN). Methods: The research team used purposeful selection to obtain a diverse sample and did ten in-depth interviews with mothers, ten with single men aged 19–24 years, and ten with single women aged 18–23 years in the West Bank. Besides general questions about child discipline, interviewers asked all participants for feedback in relation to clarity, acceptability, and relevance of the ICAST survey questions. Findings: 26 (87%) people interviewed perceived most ICAST questions as acceptable and relevant. However, their feedback suggested severe problems related to sexual abuse questions. Young women suggested that such questions could reopen emotional trauma in a context where support services are at a minimum. Many of the interviewees asked if respondents would answer these questions truthfully and warned that both interviewees and interviewers could face social repercussions. The group of 20 men and women aged 18–24 years also raised issues about child abuse and neglect that were not addressed by the ICAST surveys, such as discrimination among siblings by parents. Additionally, young people questioned whether people who are illiterate and those with mental disabilities could be included in the survey. Interpretation: In view of the absence of adequate services for psychological follow-up for victims of sexual abuse, our findings suggest that the survey in its original version could cause harm. Combined with the doubtful sensitivity of this instrument as a screening technique, our study highlights the importance of undertaking validation of research instruments before being introduced into a new cultural setting. In the Palestinian context, alternative research methods need to be considered to study issues of sexual abuse. Funding: Qatar National Research Fund.